From safety to source domination and diversity content: Media challenges in the pandemic era - Erwin Kartinawati (Universitas Negeri Yogyakarta, 2022)
All sectors of human life have been affected by the Covid-19 virus, including the media industry. There have been many changes in the media organization. The patterns that have become standard have completely changed due to the pandemic. The media face many challenges because of that. Those are the risk to the safety of workers, the loss of several types of jobs, the dominance of information sources, and threats to the diversity of information that the public can receive. Those were the results of this study. That results were obtained by a research process carried out from May to mid-December 2021. The method was carried out by interviewing and observing journalists who worked in the Surakarta area, Indonesia. Apart from that, it also observed the media work process (newsroom). Technology, the safety of life, dominance of news sources, and diversity of content were challenges for media actors in ethical demands and the fulfillment of basic principles of journalism that have not changed at all.